2015
DOI: 10.1136/annrheumdis-2015-207991
|View full text |Cite
|
Sign up to set email alerts
|

T cell subsets: an immunological biomarker to predict progression to clinical arthritis in ACPA-positive individuals

Abstract: ObjectivesAnticitrullinated protein antibody (ACPA)+ individuals with non-specific musculoskeletal symptoms are at risk of inflammatory arthritis (IA). This study aims to demonstrate the predictive value of T cell subset quantification for progression towards IA and compare it with previously identified clinical predictors of progression.Methods103 ACPA+ individuals without clinical synovitis were observed 3-monthly for 12 months and then as clinically indicated. The end point was the development of IA. Naïve,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
47
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 45 publications
8
47
1
2
Order By: Relevance
“…We established that reduced (age-normalised) frequencies of naive CD4+ T-cells in early RA at baseline were associated with failure to achieve remission with MTX treatment 22 . Furthermore, we showed that the progression towards IA from at-risk stages (ACPA + no synovitis) could be predicted using all 3 T-cell subsets 23 .…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…We established that reduced (age-normalised) frequencies of naive CD4+ T-cells in early RA at baseline were associated with failure to achieve remission with MTX treatment 22 . Furthermore, we showed that the progression towards IA from at-risk stages (ACPA + no synovitis) could be predicted using all 3 T-cell subsets 23 .…”
mentioning
confidence: 85%
“…Following 2 initial reports describing the potential of T-cell subset quantification associated with 2 stages of the IA-continuum (at-risk and response to treatment) 22,23 , in this study we describe data from 705 patients recruited at distinct stages of the IA continuum, to model the potential clinical utility of scoring T-cells subset as biomarkers predictive of progression to the next stage of the continuum, with implications for targeted management. We first, modelled the clinical value of phenotyping T-cells for the prediction of progression from one stage to the next.…”
mentioning
confidence: 99%
“…L. Hunt и соавт. [46] проанализировали риск развития РА в группе 103 АЦЦП-позитивных паци-ентов без признаков синовита. Прогрессирование забо-левания отмечалось у 46,6% больных, причем у подавля-ющего большинства -в течение первых 12 мес.…”
Section: Discussionunclassified
“…Недавно получены данные о том, что у АЦЦП-пози-тивных людей без клинических признаков артрита наблю-дается снижение числа наивных и регуляторных Т-клеток и увеличение содержания так называемых «клеток, связан-ных с воспалением» (inflammation related cells), причем комбинация этих нарушений позволяет прогнозировать риск развития РА [123]. В других исследованиях было по-казано, что у пациентов с серопозитивной артралгией (как и при серопозитивном РА) наблюдается снижение (связа-но с апоптозом) числа естественных киллерных (ЕК) кле-ток (CD56 dim ), которые при активации посредством CD16 (FcγRIIIa) начинают синтезировать широкий спектр «про-воспалительных» цитокинов [124].…”
Section: таблицаunclassified